Kepadatan Penduduk dan Kualitas Hidup: Studi Kasus di Kawasan Padat Kota Serang Banten - Muhamad Fairuz Al-farij; Ahmad Fadli Ramadani; Akrom Akrom (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to explore in depth the impact of population density on the quality of life of residents in densely populated areas of Serang City, Banten Province. The background of this research is based on the phenomenon of increasing population numbers due to ongoing urbanization and migration, which directly affects the social, economic, and environmental pressures in urban areas. This research employs a qualitative approach using a descriptive method. Data were collected through in-depth interviews with residents, community leaders, and local government officials, as well as field observations in areas with high population density. Secondary data were obtained from official documents such as reports from the Central Bureau of Statistics (BPS) and regional development planning documents. The results reveal that population density negatively affects access to basic services such as clean water, sanitation, education, and healthcare. Furthermore, it creates pressure on the living environment and reduces the comfort of residential spaces. Communities in high-density areas tend to face challenges in fulfilling basic needs adequately, which in turn impacts their overall well-being. This study highlights the importance of participatory and data-based urban planning, along with strong cross-sectoral coordination in providing social and environmental infrastructure. It is recommended that local governments develop adaptive policies in response to demographic dynamics to create livable, inclusive, and sustainable urban spaces. The findings of this research are expected to serve as a reference for future policy-making regarding the development of densely populated areas.